Planting Time Effect on Quality Seed Production of Three Varieties of Carrot (Daucus Carota L.) (Bangladesh Agronomy Journal, 2021)
Crop management like planting time is a crucial factor for maximizing yield especially for seed production. Seed production of carrot is greatly influenced by temperature as it requires adequate periods of cool temperature (vernalization) for flowering and seed production. To find out optimum planting time of carrot steckling for quality seed production the experiment was conducted at the Field Laboratory of Horticulture Farm, Bangladesh Agricultural University, Mymensingh during the period from October 2015 to May 2016.Three planting time viz. 05 January, 15 January and 25 January on the seed production of three carrot varieties viz. BA (Brasillia Agroflora), PA (Prima Agroflora) and NK (New Kuroda) which constituted 9 treatment combinations were included in the experiment. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Planting time had significant effect on most of the parameters studied. The January 05 planting of steckling gave the highest seed yield (527.92 kg ha-1) and the lowest was in January 25 planting of steckling (314.75 kg ha-1). Among the varieties BA gave the highest seed yield (448.73 kg ha-1) and the lowest yield for New Kuroda (395.35 kgha-1.) Considering interaction of planting time and variety the highest seed yield (572.37 kg ha-1) was obtained from the treatment combination of early planting (05 January) with the variety of BA and the lowest (279.77 kg ha-1) was recorded from the late planting (25 January) in variety PA. Hence, BA carrot variety planting on 5 January may be recommended for carrot seed production in Mymensingh region in Bangladesh.Bangladesh Agron. J. 2020, 23(2): 23-34